2002
DOI: 10.1002/jnr.10486
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury‐induced acute gene expression changes in rat cerebral cortex identified by GeneChip analysis

Abstract: Proper CNS function depends on concerted expression of thousands of genes in a controlled and timely manner. Traumatic brain injury (TBI) in mammals results in neuronal death and neurological dysfunction, which might be mediated by altered expression of several genes. By employing a CNS-specific GeneChip and real-time polymerase chain reaction (PCR), the present study analyzed the gene expression changes in adult rat cerebral cortex in the first 24 hr after a controlled cortical impact injury. Many functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(47 citation statements)
references
References 80 publications
6
41
0
Order By: Relevance
“…Previous array expression studies in TBI models have demonstrated that the brain mounts a specific and concerted genomic response to injury, specifically upregulating certain genes and suppressing others ( Matzilevich et al, 2002;Raghavendra et al, 2003). Because the brain is a complex multicellular organ composed of a variety of cell types that exhibit potentially divergent genomic responses to injury, analyses of whole regions or subregions of the brain will confound the specific contributions from individual neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Previous array expression studies in TBI models have demonstrated that the brain mounts a specific and concerted genomic response to injury, specifically upregulating certain genes and suppressing others ( Matzilevich et al, 2002;Raghavendra et al, 2003). Because the brain is a complex multicellular organ composed of a variety of cell types that exhibit potentially divergent genomic responses to injury, analyses of whole regions or subregions of the brain will confound the specific contributions from individual neurons.…”
Section: Discussionmentioning
confidence: 99%
“…This model reproduces many of the features of human brain injuries including motor deficits, memory loss, and neuron loss (Colicos et al, 1996). Responses following controlled cortical impact include glial activation, cytokine expression, and BBB disruption (Koshinaga et al, 2007; Raghavendra Rao et al, 2003) throughout the ipsilateral cortex and hippocampus (Smith et al, 1995). …”
Section: Introductionmentioning
confidence: 99%
“…Because SOCS-3 may also be neuroprotective as SOCS-3 and other members of SOCS family increase after focal stroke, cerebral ischemia, traumatic brain injury, and spinal chord injury (7,43) and antisense knockdown of SOCS-3 expression increases stroke size (43), we explored the role of SOCS-3 in cell survival, in response to TNF␣ and IGF-1. An 80% decrease in cell survival was observed in SOCS-3-transfected cells following IGF-1 stimulation, as compared with 20% (statistically insignificant) in the case of TNF␣ (Fig.…”
Section: Socs-3 Inhibits Cell Growth Inmentioning
confidence: 99%